Pemahaman Siswa Terhadap Bahan Ajar Muatan Lokal Bahasa Daerah Bengkulu Kelas IV SDN 04 Bengkulu (Uji Coba Bahan Ajar) - Puspo Rahayu; Resnani Resnani; Sri Ken Kustianti (JURIDIKDAS, 2019)
This study aims to describe the ability of students in understanding the local language teaching materials of Bengkulu on the subject of Local Content in the fourth grade of SDN 04 Kota Bengkulu. The research method used in this research is quantitative descriptive method with percentage technique. The study population is all students of grade IV SDN 04 Kota Bengkulu. The sample in this study is the students of grade IVB which amounted to 28 students. The sample is determined by cluster random sampling technique in the population. The research instrument used a test sheet. Data analysis technique is done by using learning result test which is adjusted to the value of KKM (Criteria Completed Minimum) subject of Local Content applicable at SDN 04 Kota Bengkulu that is equal to 67. The result of research indicate that 82,1% of students reach KKM with average value The average student is 79.46. Thus, it can be concluded that the ability of students in understanding the language of Bengkulu local language is in the good category.